2023
DOI: 10.3389/fnut.2023.1120254
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene prevents non-alcoholic fatty liver disease through regulating hepatic NF-κB/NLRP3 inflammasome pathway and intestinal microbiota in mice fed with high-fat and high-fructose diet

Abstract: Lycopene (LY) belongs to carotenoids and is abundant in red fruits and vegetables. Several previous studies suggested that LY is beneficial for ameliorating non-alcoholic fatty liver disease (NAFLD), while the potential mechanisms are unclear. The present study aimed to clarify the potential mechanisms of LY in preventing NAFLD via exploring the hepatic NF-κB/NLRP3 inflammasome pathway and intestinal microbiota composition in high-fat and high-fructose diet (HFFD)-fed mice. Fifty eight-week-old male C57BL/6J m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Lycopene affected the inflammatory signaling pathway associated with hepatic NLRP3 by reducing the expression of the liver proteins Pro-Caspase-1, Caspase-1, NLRP3, and NF-κB. The study showed that lycopene may prevent NAFLD by inhibiting the NF-κB/NLRP3 inflammasome pathway in the liver [110]. In another study, lycopene, luteolin, and their combination were shown to activate the adenosine monophosphate-activated protein kinase (AMPK) pathway.…”
Section: Antioxidant Activity Of Lycopene In Liver Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…Lycopene affected the inflammatory signaling pathway associated with hepatic NLRP3 by reducing the expression of the liver proteins Pro-Caspase-1, Caspase-1, NLRP3, and NF-κB. The study showed that lycopene may prevent NAFLD by inhibiting the NF-κB/NLRP3 inflammasome pathway in the liver [110]. In another study, lycopene, luteolin, and their combination were shown to activate the adenosine monophosphate-activated protein kinase (AMPK) pathway.…”
Section: Antioxidant Activity Of Lycopene In Liver Diseasesmentioning
confidence: 96%
“…It also increased the total antioxidant capacity (TAP) as well as SOD and CAT activity in the liver [109]. Gao et al [110] studied the effect of lycopene on the hepatic NF-κB/NLRP3 inflammasome pathway in C57BL/6J mice with NAFLD. The tested carotenoid reduced body weight gain and reduced white adipose tissue mass in mice.…”
Section: Antioxidant Activity Of Lycopene In Liver Diseasesmentioning
confidence: 99%
“…In the case of disorders that arise from cognitive decline, such as dementia, α - and β -carotene, lutein, and zeaxanthin have been associated with improved cognitive functionality [ 113 ]. On the other hand, treatment with lycopene has been demonstrated to prevent the development of NAFLD in C57BL/6J mice by suppressing the hepatic NFκ-B/NLRP3 inflammasome pathway [ 114 ]. In contrast, treatment with zeaxanthin has been shown to decrease the generation of ROS, inhibit ferroptosis, enhance mitochondrial dysfunction, and diminish lipid peroxidation in free fatty acid-induced HepG2 cells.…”
Section: Carotenoids: Sources Extraction Characterization and Activit...mentioning
confidence: 99%
“…Other studies have showed that various stimuli caused by neuroinflammatory or degenerative processes can promote the activation of NLRP3 inflammasome, thereby altering the gut microbiota ( Pellegrini et al., 2017 ). It was found that the knockout of NLRP3 could lead to the increase of Firmicutes and a decrease in Bacteroidetes in the gut of mice, as well as the increase of Lachnospiraceae , Ruminococcaceae and Prevotellaceae ( Gao et al., 2023 ). Collectively, inflammasome may be the key target for directly regulating inflammation and infectious diseases.…”
Section: Innate Immune Signaling Pathway Regulates Inflammatory and I...mentioning
confidence: 99%